Lessons of the Financial Crisis - Steil, Benn (Council on Foreign Relations: Council special report, 2009)
The current financial and economic crisis is a classic bust of a credit boom, the boom having been fueled by policies whose combined effects were to increase the demand for debt to unsustainable levels. U.S. monetary policy, taxation policy, and home ownership promotion policy were so conducive to credit expansion that the idea, understandably popular in Washington and Brussels, that preventing future such crises can be accomplished simply by waking up regulators "asleep at the switch" is dangerously simplistic. The United States in particular, given that it effectively sets monetary and credit conditions for a significant portion of the global economy, needs to put in place policies that can better discourage, recognize, and curtail a credit boom, and ensure that systemically important financial institutions can withstand its unwinding.